2003
DOI: 10.1159/000070044
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Ploidy in Regenerating Livers after Partial Hepatectomy, Drug-Induced Necrosis, and Cirrhosis

Abstract: The hepatocyte ploidy was investigated by flow cytometry in regenerating Sprague-Dawley rat livers following either drug-induced acute necrosis (single sublethal doses of D-galactosamine or thioacetamide) or drug-induced chronic cirrhosis (repeated thioacetamide injections for 10–18 weeks) and in regenerating livers following 70% partial hepatectomy and was compared with that of normal hepatocytes. Twenty-four hours after partial hepatectomy, a significant decrease in 2n (1 diploid nucleus) hepatocytes and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 58 publications
0
7
1
Order By: Relevance
“…Increased hepatocyte ploidy during liver regeneration following PHx has already been reported. [26] ACE inhibitor captopril was found to decrease the hepatocyte cellular size at 48 h after PHx during normal liver regeneration[11] whereas in this study we observed that lisinopril treatment did not affect hepatocyte nuclear or cellular area, leading to conclude that it had no effect on hepatocyte hypertrophy during fibrotic liver regeneration.…”
Section: Discussioncontrasting
confidence: 54%
“…Increased hepatocyte ploidy during liver regeneration following PHx has already been reported. [26] ACE inhibitor captopril was found to decrease the hepatocyte cellular size at 48 h after PHx during normal liver regeneration[11] whereas in this study we observed that lisinopril treatment did not affect hepatocyte nuclear or cellular area, leading to conclude that it had no effect on hepatocyte hypertrophy during fibrotic liver regeneration.…”
Section: Discussioncontrasting
confidence: 54%
“…In normal, non‐injected livers hepatocytes were arranged in hepatic plates, mostly with radian position in respect to hepatic veins or portal triads (Figure 1A). All zones of the hepatic unit showed heterogeneity in hepatocyte size, as well as minimal variations in cytoplasm density and vacuolization (Figure 1B—zone 3, Figure 1C—zone 1), which is typical for rodent liver 25, 26.…”
Section: Resultsmentioning
confidence: 95%
“…Numerous studies have shown that normal diploid cells of other lineages can be induced to undergo polyploidization via endomitosis as a consequence of stress (e.g., hypertension and senescence (reviewed in Ravid et al (2002))). In addition, polyploid hepatocytes have been described to increase in number dramatically upon oxidative stress or after partial hepatoectomy (Dethloff and de la Iglesia, 1998; Gupta, 2000; Gandillet et al, 2003). Endothelial cells and fibroblasts have been shown in tissue biopsies and in cell culture to become polyploid upon aging and during tissue repair (Oberringer et al, 1999; Wagner et al, 2001).…”
Section: Overview: Characteristics Of Tetraploidy and Aneuploidy And mentioning
confidence: 99%